Sambandet mellan svenska elitlängdskidåkares kroppsvikt och tävlingsprestation - Löfström, H. (Högskolan Dalarna, 2018)
Purpose statement: The purpose of the study is to examine if Swedish elite cross-country skiers body mass is correlated to the results on competitions.